Analisis Komparatif Kinerja Keuangan Bank Syariah Sebelum dan Selama Pandemi Covid-19 - Muhammad Rif'at Wijdan; Tjetjep Djuwarsa; Benny Barnas (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
The entry of Covid-19 into Indonesia caused a decline in economic growth in Indonesia and disruption to the banking sector, resulting in the risk of declining profitability, liquidity difficulties, decreased profitability, and growth that slowed down the decline in bank performance. The purpose of this study was to compare the differences in the financial performance of Islamic banking before and during the COVID-19 pandemic. In this study used financial performance ratios, financial performance consists of FDR, CAR, NPF, BOPO and ROA. The population of this study were eight Islamic banks listed at the OJK. The discussion was carried out using multiple linear regression and the Sing-Wilcoxon difference test. The results showed that there was an effect of CAR, NPF, and BOPO except FDR on ROA, and there were also significant differences that were not shown by CAR, while ROA, NPF, BOPO, and FDR showed significant differences before and during Covid-19 . From these results, it can be said that there is an impact of Covid-19 on the financial performance of Islamic banks in Indonesia.